Posted by **jessica** on Wednesday, April 4, 2007 at 1:03am.

Solve for s in this equation. Depreciation. D=C-s/n

This is my answer D-C=C-s/n-c

D-C=-s/n

-n(D-C)=-s/n*(-n)

-nD+nC=s

s=n(C-D)

Please chack to see if this is correct

Looks fine to me. A slightly shorter (by 2 lines) rearragement is:

D=C-s/n

D+s/n=C

s/n=C-D

s=n(C-D)

but hey, you got there!

Thanks for the review. I thought the answer was right, but my algebra tacher said it was wrong

wrong because of the wrong answer, or wrong because of the wrong method? Best check with the teacher.

it is wrong! the s is still negative so the real answer is D+C=s

I don't understand. Where is the n in your answer?

Also it is not possible to rearrange D+C=s back to:

D=C-s/n

She said that the first step was wrong